Positive cardiac inotropic effect of albumin infusion in rodents with cirrhosis and ascites: molecular mechanisms1. Issue 1 (7th January 2013) - Bortoluzzi, Alessia; Ceolotto, Giulio; Gola, Elisabetta; Sticca, Antonietta; Bova, Sergio; Morando, Filippo; Piano, Salvatore; Fasolato, Silvano; Rosi, Silvia; Gatta, Angelo; Angeli, Paolo
Abstract The aim of this study was to evaluate the effect and molecular mechanism of albumin infusion on cardiac contractility in experimental cirrhosis with ascites. Cardiac contractility was recorded ex vivo in rats with cirrhosis and ascites and in control rats after the injection in the caudal vein of albumin, saline, or hydroxyethyl starch (HES). Gene and protein expression of β‐receptors and pathways involved in their intracellular signaling such as Gαi2 protein (Gαi2), adenylate cyclase 3 (Adcy3), protein expression of tumor necrosis factor alpha (TNF‐α) and inducible nitric oxide synthase (iNOS), were evaluated in cardiac tissue in both groups. Phosphorylation and membrane‐translocation of the cytosolic components of nicotinamide adenine dinucleotide phosphate (NAD(P)H)‐oxidase and translocation of nuclear factor kappa B (NF‐κB) were also evaluated. After saline intravenous injection, cardiac contractility was significantly reduced in rats with cirrhosis as compared to control rats (P < 0.01). This was associated with: (1) increased expression of protein Gαi2 (P < 0.05), TNF‐α (P < 0.05), iNOS (P < 0.05); (2) increased NAD(P)H‐oxidase activity (P < 0.05); (3) increased nuclear translocation of NF‐κB (P < 0.05); and (4) lower expression of Adcy 3 (P < 0.05) in cardiac tissue of rats with cirrhosis. After albumin injection cardiac contractility (P < 0.01), protein expression of TNF‐α, iNOS, Gαi2, and Adcy3, NAD(P)H‐oxidase activity and nuclear translocation of NF‐κB in cardiac tissue of rats with cirrhosis were reversed to control levels (P < 0.05). HES injection did not modify cardiac contractility and nuclear translocation of NF‐κB in cardiac tissue of rats with cirrhosis. Conclusion: Albumin exerts a positive cardiac inotropic effect in rats with cirrhosis and ascites counteracting the negative effects of oxidative stress‐ and TNF‐α‐induced activation of NF‐κB‐iNOS pathway and oxidative stress‐induced alteration of β‐receptor signaling. (HEPATOLOGY 2013)